Markers of treatment failure in hospitalised community acquired pneumonia. Issue 5 (1st February 2008) - Menéndez, R; Cavalcanti, M; Reyes, S; Mensa, J; Martinez, R; Marcos, M A; Filella, X; Niederman, M; Torres, A
Abstract : Background: Lack of response to treatment in community acquired pneumonia (CAP) worsens outcome. We evaluated the systemic cytokine profile (tumour necrosis factor α, interleukin (IL)1, IL6, IL8 and IL10), C reactive protein (CRP) and procalcitonin (PCT) in patients with CAP who had treatment failure. Methods: A prospective study was performed in hospitalised patients with CAP. Cytokines, PCT and CRP measurements were obtained on day 1 and after 72 h of treatment. Treatment failure was the endpoint evaluated, with separation of those with early (⩽72 h) or late failure. Results: 453 patients were included: 84 (18%) had treatment failure, of whom 38 (8%) were early failures. Median levels of IL6, PCT and CRP on days 1 and 3 and median levels of IL8 on day 1 were significantly higher in patients with any treatment failure. Logistic regression analysis demonstrated that values above the cut-off points for IL6 (⩾169 pg/ml), IL8 (⩾14 pg/ml) and CRP (⩾21.9 mg/dl) on day 1 had independent predictive value for any treatment failure after adjustment for initial severity; relative risks (OR) found were 1.9, 2.2 and 2.6, respectively. Increased levels for CRP and PCT on day 1 were also independent predictors for early failure. Increased levels for IL6 and CRP were the best predictors of late failure. Conclusions: Serum levels of CRP, IL6 and PCT on days 1 and 3 were independently associated with a higher risk of any treatment failure. Low levels of PCT and CRP on day 1 had a high negative predictive value for early failure.